WHY UZBEKISTAN SHOULD ADOPT ESG IN CORPORATE GOVERNANCE (International Conference on Economics, Finance, Banking and Management, 2025)
In the context of global economic transformation and rising investor awareness, Environmental, Social, and Governance (ESG) standards are becoming critical benchmarks for corporate responsibility and performance. This thesis argues for the urgent need for Uzbekistan to adopt ESG principles in corporate governance to ensure sustainable development, attract foreign investment, and enhance market competitiveness. While Uzbekistan has committed to ambitious environmental and social targets — including a 40% renewable energy share and a 30% reduction in greenhouse gas emissions by 2030 — actual corporate alignment with these goals remains low. Integrating ESG into governance frameworks can bridge this gap by formalizing transparency, risk management, and accountability mechanisms in both public and private enterprises. The issuance of green bonds in 2023 signals progress, yet broader regulatory and institutional adoption is needed. ESG implementation not only strengthens corporate governance but also provides a pathway for Uzbek companies to integrate into responsible global supply chains and secure long-term growth. This paper explores how adopting ESG frameworks can catalyze systemic change across industries, support the country's green transition, and position Uzbekistan as a credible and resilient emerging market.